2021
DOI: 10.1002/chem.202004828
|View full text |Cite
|
Sign up to set email alerts
|

Proanthocyanin‐Capped Biogenic TiO2 Nanoparticles with Enhanced Penetration, Antibacterial and ROS Mediated Inhibition of Bacteria Proliferation and Biofilm Formation: A Comparative Approach

Abstract: Biofunctionalized TiO 2 nanoparticles with as ize range of 18.42 AE 1.3 nm were synthesized in asingle-step approach employing Grape seed extract (GSE) proanthocyanin (PAC) polyphenols. The effect of PACs rich GSE coronaw as examined with respectt o1)the stability and dispersity of as-synthesized GSE-TiO 2-NPs, 2) their antiproliferativeand antibiofilm efficacy,a nd 3) their propensity fori nternalization and reactive oxygen species (ROS) generation in urinary tract infections (UTIs) causing Gram-negative Pseu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 75 publications
0
18
0
Order By: Relevance
“… 56 The structural difference in cell walls of bacteria is the combination of biological layer and peptidoglycan layer, phospholipid layer, lipopolysaccharide layer and peptidoglycan layer respectively. 57 The researchers found that the AgNPs adhere stably to the bacterial cell wall and penetrate the bacteria, inducing cell death by destroying the cell membrane. 58…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 56 The structural difference in cell walls of bacteria is the combination of biological layer and peptidoglycan layer, phospholipid layer, lipopolysaccharide layer and peptidoglycan layer respectively. 57 The researchers found that the AgNPs adhere stably to the bacterial cell wall and penetrate the bacteria, inducing cell death by destroying the cell membrane. 58…”
Section: Resultsmentioning
confidence: 99%
“…layer and peptidoglycan layer respectively. 57 The researchers found that the AgNPs adhere stably to the bacterial cell wall and penetrate the bacteria, inducing cell death by destroying the cell membrane. 58 The MIC is often used as a significant indicator of antibacterial efficacy.…”
mentioning
confidence: 99%
“…The growing pursuits in metal-based nanomaterials synthesis are hotly debated in several fields while acknowledging their unique physico-chemical and biomedical properties with specific advocacy for fitness in clinical settings as fascinating treatment modality, worldwide [1]. Considering that there is a wide scope to achieve desired properties in synthesized nanoparticles (NPs) including shape, size and stability by manipulating reaction conditions such as pH, temperature, concentration of metal precursors and concentration and nature of bio-reducing agents [2][3][4][5][6][7][8]. Besides, surface capping or encapsulation material of NPs deserves special importance due to being directly or indirectly concerned with limiting toxicity and cations release, affinities towards miscellaneous components of immediate environment, and cells surface, enhanced dispersity and prolonged stability and enhanced internalization propensity in several cells [5,9].…”
Section: Introductionmentioning
confidence: 99%
“…Such nanoscale fabrication of organic, inorganic, metallic, and biological structures is generally done by following either bottom-up or top-down approaches. In modern times, green approaches for NPs synthesis have gained immense interest due to its eco-friendly processing and low-cost input [ 10 , 11 , 12 ]. Furthermore, NPs derived from various plant extracts contain a variety of indigenous bio-active molecules such as polyphenols, alkaloids, terpenoids, sugars, proteins, and enzymes that act as reducing, capping, and stabilizing agents.…”
Section: Introductionmentioning
confidence: 99%